The scripture on great peace : the Taiping jing and the beginnings of Daoism - Hendrischke, Barbara, 1940- (Berkeley : University of California Press, 2006)
This first Western-language translation of one of the great books of the Daoist religious tradition, the Taiping jing, or ''Scripture on Great Peace, '' documents early Chinese medieval thought and lays the groundwork for a more complete understanding of Daoism's origins. Barbara Hendrischke, a leading expert on the Taiping jing in the West, has spent twenty-five years on this magisterial translation, which includes notes that contextualize the scripture's political and religious significance. Virtually unknown to scholars until the 1970s, the Taiping jing raises the hope for salvation in a pra.
Section 50. An Explanation of the Master's DeclarationSection 51. The True Contract; Section 52. How to Work Hard to Do Good; Section 53. How to Distinguish between Root and Branches; Section 54. How to Enjoy Giving Life Wins Favor with Heaven; Section 55. How to Classify Old Texts and Give a Title to theBook; Section 56. How the Nine Groups of Men Disperse CalamitiesInherited from Former Kings; Section 57. How to Examine What Is True and What Is False Dao; S.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Tai ping jing; Tai ping jing; Taoism -- Early works to 1800.; Philosophy, Chinese; Taoïsme -- Ouvrages avant 1800.; Philosophie chinoise; RELIGION -- Taoism; BODY, MIND & SPIRIT -- Spirituality -- Paganism & Neo-Paganism.; RELIGION -- Comparative Religion; Philosophy, Chinese; Taoism; Computer network resources; Early works